PERDAMAIAN GEJOLAK PENCABUTAN IZIN RUMAH IBADAH DI BANTUL - Enggar Wijayanto; Wahidul Halim; Faiq Tobroni (LPPM IAIN Sorong, 2020)
Sometimes when a permit for house of worship is revoked in one religion, the issue that arises is intolerance from the majority religious interest groups towards minorities. This kind of impression has also been heard when there was a church license revocation in Bantul, where there was a narrative that the Muslim majority group was intolerant towards Christian minority groups. This research found that the revocation of the permit for places of worship was legality under statutory regulations, which in this case it is the Bantul Regent Regulation. Although indeed it is debatable. But at the very least, the use of state law as a consideration for revoking a religious place of worship is a strategy to avoid prolonged inter-religious conflict.